Ligand-free Ullmann-type arylation of oxazolidinones by diaryliodonium salts. Issue 9 (9th February 2023) - Podrezova, Ekaterina V.; Okhina, Alina A.; Rogachev, Artem D.; Baykov, Sergey V.; Kirschning, Andreas; Yusubov, Mekhman S.; Soldatova, Natalia S.; Postnikov, Pavel S.
Abstract : The arylation of azaheterocycles can be considered as one of the most important processes for the preparation of various biologically active compounds. Abstract : The arylation of azaheterocycles can be considered as one of the most important processes for the preparation of various biologically active compounds. In the present work, we describe a method for the copper-catalyzed N -arylation of hindered oxazolidinones using diaryliodonium salts. The method succeeds in good to excellent yields for the arylation of 4-alkyloxazolidinones, including sterically hindered isopropyl- and tert -butyl-substituted. The efficiency of the method was demonstrated for a wide range of diaryliodonium salts – symmetric and unsymmetric as well as ortho -substituted derivatives. The developed approach will provide an important contribution in the development and preparation of novel drugs and bioactive molecules containing oxazolidinone moieties.